Capacity selection for hubs and hub links in hub location problems. Issue 3 (2nd July 2016) - Rastani, Sina; Setak, Mostafa; Karimi, Hossein
Abstract : Hub location problems occur mainly in transportation and telecommunications networks. A hub is a transfer point at which either traffic from several origins is added up and forwarded to another hub, or disaggregated into several streams that are forwarded to their destinations. The hub location problem is concerned with locating hub facilities and allocating demand nodes to hubs in order to route the traffic between origin–destination pairs. In this research, a hub network with capacity constraints on the hubs and hub links (i.e. links which connect hubs to each other) is considered. These capacities are multi-level capacities, so hubs and hub links should take a capacity among a set of capacities. In real-world examples, such as designing a transportation network, the costs of establishing hubs and hub links are momentous in the decision making process. Consequently, as the capacity is used more, the costs of using hubs and hub links increase. In this research, a formulation is presented for the proposed model and its computational results are compared with single-level capacity problems.